Knowledge communication and non-communication in the water governance of the Saemangeum area, South Korea. (10th July 2017) - Kim, KoUn; Shin, HaeRan; Kim, Miseon; Chang, Chuyoun
Abstract: This paper looks at how knowledge has been communicated within a multi-layered water governance structure in order to manage non-point source (NPS) pollution in South Korea. Since 28, 300 ha of wetlands were reclaimed in Saemangeum, on the western side of the country, in 2006, the artificial lake created has suffered from chronic pollution. For the purposes of integrated water management, a water governance structure was formed linking organisations ranging from local to national scales. Despite institutional efforts to implement integrated water management and a governance approach, knowledge of NPS pollution and its management was produced and communicated among certain stakeholders only, such as policy and technical experts. In-depth interview and archival analysis of this research attempt to explain why and how the loss of knowledge communication occurred in this context. The first result of this research illustrates that, while knowledge communication has been smooth at the national and provincial layers, it has not taken place efficiently through to the local layer. When it comes to local farmers and governmental organisations and experts in particular, knowledge nodes have not functioned. Second, the research suggests that non-communication of knowledge has been mobilised as a professional strategy. Actors at the local layer have prioritized their professional interests and intentionally avoided knowledge communication with other department or ministries. Local and community actors have chosen not to provide farmers information. We conclude by discussing policy implications for knowledge communication and inclusive water governance.